2021
DOI: 10.1186/s12917-021-03021-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of Leishmaniasis in the rural area of the western border region of Rio Grande do Sul, Brazil

Abstract: Background The Leishmaniases are on the top of the global list of tropical neglected diseases. The number of infected dogs in South America is estimated in millions and correlated to disease cases in humans, especially in Brazil. Equines may get infected too and can play a role in the epidemiological chain. Thus, the aim of the present study was to evaluate risk and protective factors of leishmaniasis in rural areas of the western border region of Rio Grande do Sul state, Brazil by Leishmania s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The presence of L. infantum in the Brazil-Argentina-Uruguay transborder region was only discovered recently: until the past decade, this infection had never been diagnosed in southern Brazil. In addition, canine and human leishmaniasis cases have now been detected, as well as infections among horses (Escobar et al, 2019;Pradella et al, 2020Pradella et al, , 2021. This border region was not previously included as a focus of the federal healthcare system and it was believed that the disease would be cutaneous and not visceral, as studies had shown.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of L. infantum in the Brazil-Argentina-Uruguay transborder region was only discovered recently: until the past decade, this infection had never been diagnosed in southern Brazil. In addition, canine and human leishmaniasis cases have now been detected, as well as infections among horses (Escobar et al, 2019;Pradella et al, 2020Pradella et al, , 2021. This border region was not previously included as a focus of the federal healthcare system and it was believed that the disease would be cutaneous and not visceral, as studies had shown.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock was included to incorporate possible animal reservoirs which may influence the distribution and incidence of VL. Numerous mammals such as chickens [28,29], swine [30], horses [31,32] and cattle [10] have been documented as blood sources for sandflies in Brazil and thus serve as possible reservoirs. Livestock production for buffalo and quail were also PLOS NEGLECTED TROPICAL DISEASES available but were omitted from the analysis due to a lack of spatial heterogeneity.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%